(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
In the present work there are examined the principal limitations from which there suffers the decennial assurance of damages of the building, since in the Law38/1999, of November 5, of Arrangement of the Building this guarantee turns out tobe formed in a very particular way (art. 19 LOE). Besides, there is imposed the obligationto sign assurances only to the agents of the building, without of parallel form such a exigency is established to the insurance entities and it is freed from the fulfillment of this guarantee to the buildings in which the promoter is a public Administration(art. 1.3 LOE).Finally, the scope of the decennial assurance has remained restricted furthermore with the modification produced across the article 105 of the Law 53/2002, of December 30, of Fiscal, Administrative Measurements and of the Social Order,which it excludes from the obligation to sign the obligatory guarantees the suppositionsof individual autopromotion and building rehabilitation.